Food price changes and consumer welfare in Tanzania 1991 - 2007 - Vincent Leyaro; Oliver Morrissey; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2010)
This paper analyses the effect of food price changes on household consumption (welfare) in Tanzania during the 1990s and 2000s, and simulates the welfare effect attributable to tax (tariffs and VAT) reforms, distinguishing both static (first order) and dynamic (full price) effects of price changes. The three rounds of the Tanzania Household Budget Survey (1991/92, 2000/01 and 2007) are used to estimate consumers'responses using Deaton's method, based on median unit values (prices) and household budget shares. These are then utilized, first to evaluate the distributional impacts of the relative food price changes on consumer welfare in terms of compensating variation and secondly to organise the households into quintiles to simulate the effect of indirect (tariffs and VAT) tax changes on consumer welfare. The results indicate that, in real terms, price increases have worsened the welfare of most consumers during the 1990s and 2000s; the poor, in particular the rural poor, bore much of the brunt compared to the non-poor (in particular the urban non-poor). The welfare losses in the 2000s were greater than those in the 1990s. Although we cannot establish explicit links between tax reforms and domestic food price changes, the simulation shows that tax reforms tended to offset the welfare losses for all household groups. However, the non-poor and urban poor benefit more in relative terms from tax reforms; the rural poor benefit least (and to the extent that pass through is incomplete we overstate the benefit to rural households).
Keywords: H20; H31; O55; 330; Price Changes; Consumer Welfare; Tariff Reforms; Tanzania; Nahrungsmittelversorgung; Nahrungsmittelpreis; Privater Haushalt; Steuerpolitik; Soziale Lage; Tansania